"Tu mihi…": variaciones bucólicas sobre un ritual de dedicatoria, de Virgilio a Góngora - Béhar, Roland (El Colegio de México, 2013)
When Garcilaso de la Vega wrote his dedication for his first Égloga (“El dulce lamentar…”), he not only copied from Virgil’s eighth Bucolic but also from Sannazaro’s fifth Ecloga Piscatoria. This paper aims to show how important this second model became for Garcilaso’s followers.Garcilaso’s “triadic pattern” makes the hunting motive, already present in Sannazaro but not in Virgil, more prominent an element. It is central both in the dedication of Gongora’s first Soledad and in that of his Polifemo –which highlights how much the poet of Córdobais indebted to Sannazaro’s Neapolitan model of piscatory eclogue.